On the classification of functions integrable on a segment - Motornaya, O. V.; Motornyi, V. P.; Sedunova, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
The problem of classification of functions integrable on a segment is considered. Estimates for the integral moduli of continuity of functions from generalized Potapov’s classes are obtained.